Ethical aspects of clinical decision-making. Issue 2 (June 1981) - Kollemorten, I; Strandberg, C; Thomsen, B M; Wiberg, O; Windfeld-Schmidt, T; Binder, V; Elsborg, L; Hendriksen, C; Kristensen, E; Madsen, J R; Rasmussen, M K; Willumsen, L; et al.
Abstract : The aim of the present investigation was to describe and to classify significant ethical problems encountered by the members of the staff during the daily clinical work at a hospital medical department. A set of definitions was prepared for the purpose, including the definition of a 'significant ethical problem'. During a three month period 426 inpatients and 173 outpatients were admitted. Significant ethical problems were encountered during the management of 106 in-patients (25 per cent) and 9 out-patients (5 per cent). No significant difference was found between the frequency of ethical problems in female and male patients, but a positive correlation was noted between the number of problems and the patients' age. The problem types were classified according to a problem list. The results of this investigation suggest that greater attention must be paid to discussions about ethical problems among doctors and other categories of health personnel and that, among others, medical students ought to be taught the analysis of ethical problems.